Review of Effectiveness of Schedule Management Planning in Project Success: A Comprehensive Analysis of Schedule Management Planning in Project Success (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The execution of a project requires appropriate management and planning. This can be done using proper scheduling for the task in an appropriate way to achieve the desired results. In this context, many studies have focused on time and cost management techniques that can be performed under the plan. Other studies focused upon the problem of resource constraint which has emerged as the critical issue in the domain. In this context, the present study reviews the effectiveness of schedule management planning. Using the studies of the past 15 years, the researcher shows the effectiveness of schedule management planning in the project success.